Penyediaan Fasiliti Orang Kurang Upaya (OKU) Di Institut Memandu - Jauhari, Dzul Amin; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2021)
A driving institute or more generally known as driving school is a place for an individual to learn driving skill and its law regardless of the person’s condition. The disabled however will face a difficulty of movement while taking the driving lesson and test if the driving institute failed to provide the required facilities. Therefore, this study is conducted in the intention to identify the factors influencing the lack of special need facilities. The challenges in providing the facilities is also review and step to encourage diving institute to provide the facilities is also examined. The study is conducted in Perak within the Larut Matang Selama District. The method used for the study is literature review and qualitative survey through the use of partial or semi-structured interview question. Three respondents were involved in this study consisting of the management of driving institute. Through this study, financial, design, and need were found as the factor that limits the provision of the facilities for the disabled. The challenges found during the study are financial, need and maintenance. Among the measure taken to encourage the provision of said facilities is to provide the facilities to the institute, assistance the student with disabilities and law enforcement. Therefore, this study is important in focusing to improve the provision required by the disabled as well as providing comfort to them in obtaining their driving license.